Toward Multitasking Pharmacological COX-Targeting Agents: Non-Steroidal Anti-Inflammatory Prodrugs with Antiproliferative Effects - Fedora Grande; Francesca Giordano; Maria Antonietta Occhiuzzi; Carmine Rocca; Giuseppina Ioele; Michele De Luca; Gaetano Ragno; Maria Luisa Panno; Bruno Rizzuti; Antonio Garofalo (Molecules, 2021)
The antitumor activity of certain anti-inflammatory drugs is often attributed to an indirect effect based on the inhibition of COX enzymes. In the case of anti-inflammatory prodrugs, this property could be attributed to the parent molecules with mechanism other than COX inhibition, particularly through formulations capable of slowing down their metabolic conversion. In this work, a pilot docking study aimed at comparing the interaction of two prodrugs, nabumetone (NB) and its tricyclic analog 7-methoxy-2,3-dihydro-1H-cyclopenta[b]naphthalen-1-one (MC), and their common active metabolite 6-methoxy-2-naphthylacetic acid (MNA) with the COX binding site, was carried out. Cytotoxicity, cytofluorimetry, and protein expression assays on prodrugs were also performed to assess their potential as antiproliferative agents that could help hypothesize an effective use as anticancer therapeutics. Encouraging results suggest that the studied compounds could act not only as precursors of the anti-inflammatory metabolite, but also as direct antiproliferative agents.